Are mothers a source of support for women entering fertility treatment?. Issue 7 (3rd July 2018) - Skvirsky, Vera; Taubman – Ben-Ari, Orit; Shlomo, Shirley Ben; Azuri, Joseph; Horowitz, Eran
ABSTRACT: The significance of the mother–daughter dyad in coping with stressful circumstances led us to examine (a) the associations between the mental health of women entering fertility treatment ( n = 137; 76 aged 20–34; 61 aged 35–44) and the perceived type of support they receive from their mothers; (b) whether mental health is associated with age, and whether this association is moderated by the type of mother's support. We found that women perceiving more active engagement from their mothers reported greater well-being and less distress, whereas higher mothers' overprotection was associated with greater distress. Active engagement and protective buffering moderated the association between age and mental health.